MORAL METAPHYSICS IN RELIGIOUS PHILOSOPHY: A DIALOGUE BETWEEN CONFUCIUS AND KANT - Jiang, Guojun (European journal for philosophy of religion, 2025)
This study explores the possibility of a philosophical dialogue between Confucius and Kant on moral metaphysics, focusing on their respective understandings of the foundations of morality, ethical duty, and the ultimate purpose of moral life. While Kant’s moral philosophy is grounded in a rigorous metaphysical system of reason and autonomy, Confucius presents morality as an embodied practice, deeply intertwined with social harmony, ritual propriety (li), and human-heartedness (ren). Despite their differing philosophical frameworks—one rooted in Western rationalism and the other in Confucian ethical humanism—their moral inquiries share fundamental concerns regarding the cultivation of virtue, the role of moral education, and the struggle against moral decay. This article engages in a comparative analysis of Kantian and Confucian moral thought by examining their respective approaches to moral self-cultivation, duty, and the metaphysical grounding of ethics. Through a cross-examination of their ethical philosophies, the study aims to reveal their commonalities and divergences in moral construction, particularly in relation to the role of divine will, moral autonomy, and the ultimate purpose of ethical life. By situating this dialogue within the broader discourse of religious philosophy, the paper highlights how Confucius and Kant contribute to ongoing debates about the relationship between morality, metaphysics, and religious belief. It further explores whether Kant’s categorical imperative and Confucius’ virtue ethics can be reconciled in a philosophical framework that bridges Eastern and Western moral traditions. This study offers a fresh perspective on the universal and context-specific aspects of moral metaphysics, contributing to the dialogue between religious philosophy, ethics, and cross-cultural moral reasoning.